Synapsis and recombination of autosomes and sex chromosomes in two terns (Sternidae, Charadriiformes, Aves) - A. P. Lisachov; L. P. Malinovskaya; A. V. Druzyaka; P. M. Borodin; A. A. Torgasheva (Вавиловский журнал генетики и селекции)
The frequency of recombination and the patterns of crossover site distribution along the chromosomes vary considerably among animal species, including closely related species. Several hypotheses concerning the adaptive value and evolution of these variations were proposed. It was supposed that the recombination patterns of the species’ genomes are influenced by their phylogenetic history and ecology. However, most original data were obtained from mammals. The mammals show high karyological variability, which strongly influences the recombination patterns. Therefore it is important to study recombination rate and distribution in more karyologically stable taxa, such as reptiles and birds. We used immunolocalization of SYCP3, the protein of the lateral element of the synaptonemal complex (SC), centromere proteins and the mismatch-repair protein MLH1, which is associated with the recombination nodules, at the synaptonemal complex spreads of prophase oocytes of two tern species, black tern (Chlidonias niger) and common tern (Sterna hirundo). We first described the karyotype of Ch. niger (2n = 74, FN= 94) and identified suggestive rearrangements by which its karyotype differs from that of S. hirundo (2n = 68, FN = 90). We found that these species significantly differed by the numbers of the MLH1 foci per cell (Ch. niger: 53.0±4.2; S. hirundo: 44.1±5.0). We showed that the difference in the crossover numbers per cell was determined by the difference in the SC length (total and of individual bivalents) and by chromosomal rearrangements, which also influenced the distributions of crossover sites along the chromosomes. The difference in recombination patterns was higher between the rearranged homeologues than between the non-rearranged ones. We investigated the synaptic patterns of the heteromor phic Z and W chromosomes, localized the pseudoautosomal regions and estimated their lengths. In spite of several autosomal rearrangements, which differentiate these species, the structure and synaptic patterns of the sex chromosomes have not changed over 9 MY, which have passed since the moment of divergence between the genera Sterna and Chlidonias.